2011
DOI: 10.1590/s0100-736x2011001200014
|View full text |Cite
|
Sign up to set email alerts
|

Histologia, histoquímica e histometria do intestino de jacaré-do-Pantanal criado em cativeiro

Abstract: A criação de jacaré-do-Pantanal tem se consolidado no estado de Mato Grosso como atividade alternativa e legal para as propriedades rurais na área de ocorrência natural da espécie, coibindo a caça predatória e colaborando na preservação da espécie. A racionalização do processo produtivo na criação de jacaré é uma ação relativamente nova, que permite obter pele de melhor qualidade e de utilização integral, diferentemente daquelas oriundas de animais da natureza. Considerando a importância dos intestinos como se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
1
4
0
1
Order By: Relevance
“…The absence of villi in the colon of G. microtarus agrees with that described in D. aurita (Santos et al, 2013). Illanes et al (2006) in ostrich and Aleixo et al (2011) in the Pantanal's alligator observed the presence of folds or villi in the large intestine. This characteristic was not observed in the present study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The absence of villi in the colon of G. microtarus agrees with that described in D. aurita (Santos et al, 2013). Illanes et al (2006) in ostrich and Aleixo et al (2011) in the Pantanal's alligator observed the presence of folds or villi in the large intestine. This characteristic was not observed in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…The digitiform villi have also been described by Banks (1992) in the small intestine of horses and by Ribeiro et al (2011) in the small intestine of D. aurita. Aleixo et al (2011) observed bifurcate and irregular villi in the Pantanal's alligator. The myenteric ganglia were also observed in the muscular layer, between the external longitudinal and internal circular portions in the present study.…”
Section: Discussionmentioning
confidence: 96%
“…The cranial portion of the intestine, regarding the small intestine, showed numerous high, filiform and branched villi. In the mucosa, there was simple columnar epithelium formed by numerous goblet cells, structures similar to those found in green turtles (Magalhães et al., ) and different from those found in marsh alligators raised in captivity (Aleixo et al., ), which had finger‐shaped villi. Below that was found the lamina propria of the mucosa, which was thick and had secretory units formed by cuboidal cells; the muscularis mucosae and submucosa were not very visible, and the muscular layer had inner circular and outer longitudinal extracts, similar to that of young ostriches (Monteiro et al., ) (Fig.…”
Section: Resultsmentioning
confidence: 68%
“…Following, the material obtained was fixed in Bouin solution (75 % saturated picric acid solution, 25% formaldehyde and 5% glacial acetic acid) for a period of 24 hours (Eigenheer- Moreira et al 2007, Moraes et al 2007, Aleixo et al 2011. Then, the samples were dehydrated with increasing concentrations of ethanol, cleared in xylene and included in paraffin (Drummond et al 2004).…”
Section: Histological Preparationmentioning
confidence: 99%